154k views
0 votes
Create an exponential equation from the points: (1, -6) & (2, -12)

(**Make sure you start it with f(x) and include parentheses)

User Jabs
by
5.3k points

1 Answer

4 votes

The exponential equation is
f(x)=-3(2)^x

Step-by-step explanation:

The points are
$(1,-6)$ and
$(2,-12)$

To determine the exponential equation, let us substitute the points in the exponential equation
y=a(b)^x

Substituting
$(1,-6)$ in the equation
y=a(b)^x, we get,


-6=a(b)^1


-6=ab


(-6)/(b) =a

Thus, substituting
(-6)/(b) =a and
$(2,-12)$ in
y=a(b)^x, we have,


-12=(-6)/(b) (b)^2


-12=-6b


2=b

Substituting
b=2 in
(-6)/(b) =a, we get,


(-6)/(2) =a\\


-3=a

Hence, substituting the value of a and b in the exponential equation
y=a(b)^x, we have,


y=-3(2)^x

Thus, the exponential equation is
f(x)=-3(2)^x

User Annakata
by
5.2k points